Seventh Five Year Plan 1985-90 and Draft Annual Plan 1986-87 Volume—I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1985)
The Union Territory of Andaman and Nicobar Islands consists of 556 small and big Islands, including rocks, with a total geographical area of 8293 Sq. Kms and a population of 1,88,741 as per the 1981 Census. The Islands are not only separated by a vast stretch of sea from the mainland but also from each other, the distance between the Northern and Southern tips being 700 kms or so.
Andaman and Nicobar Administration